Soil Quality Indicators in an Ultisol Subjected to Chiseling in a Sugarcane Crop Under Mechanized Management in Southeastern Brazil - Pinheiro, Daniel Pereira (2021)
Soil chiseling conducted only in the planting row is a minimal-disturbance soil management practice used for soil preparation in sugarcane plantations. However, the impacts of this practice on soil physical quality need to be evaluated through agricultural experimentation. The objective of this study was to evaluate the physical quality of an Ultisol submitted to chiseling as part of sugarcane management. The treatments consisted of soil chiseling only in the planting row (CPR) and chiseling in the total area of the soil (CTA). After soil preparation, the planting rows that were submitted to chiseling had better soil physical quality than did the area between the rows that did not receive chiseling in site preparation due to greater pore volume and lower PR and BD. However, the beneficial effect of chiseling did not persist due to subsequent soil reconsolidation, and disappeared soon after the planting of sugarcane, and remained this way up to the post-harvest period wherein the areas within (CPR) and between (CTA) the planting rows had equal soil physical quality. Because of this, the yield of stalks between the two treatments were similar, with an average yield of 110 t ha−1.